Analysing the Possibility of Extracting Energy from Ocean Waves in Cabo-Verde to Produce Clean Electricity - Case-Study: the Leeward Islands - Wilson Madaleno Leger Monteiro; António Sarmento (International Journal of Renewable Energy Development, 2019)
This work analyses the possibility of extracting energy from the ocean waves around the Leeward Islands of Cabo-Verde. This study was based on 31 years of wave and wind data, obtained through the SOWFIA - Streamlining of Ocean Wave Farm Impact Assessment, at 16° N-24° W. Then, the SWAN - Simulating Waves Nearshores - was used to perform the wave transformations to the shore. As the number of waves is very high, the cluster analysis and the Non-Parametric Wilcoxon Test were used to reduce the computing time by SWAN. The results pointed to the South of these islands and the East Coast of Maio island as the best locations for wave energy extraction. The use of the power matrix of some commercial devices that are available, such as Wave Dragon (7 MW), Pelamis (750 kW) and AquaBuoy (250 kW), allowed to estimate the best devices scale factors that leads to their best Capacity Factor (CF), at the target regions. Thus, the Wave Dragon is the most indicated device (CF=71%), at the scale of 0.3, followed by AquaBuoy scaled by 0.4 (CF=57%) and Pelamis scaled by 0.5, with CF=26%. However, in a natural scale, AquaBuoy is the most efficient device (CF = 18.8%) in comparison to the Wave Dragon (CF=17%) and Pelamis (CF=15%). AquaBuoy presented the best cost-benefit ratio (C/B = 0.135 USD/kWh) followed by Wave Dragon (C/B= 0.235 USD/kWh) and Pelamis (C/B = 0.390 USD/kWh). The limitation of the number of Wave Energy Converters to implement the wave power plant affects negatively the cost of its investment.©2019. CBIORE-IJRED. All rights reservedArticle History: Received March 27th 2018; Received in revised form October 16th 2018; Accepted January 5th 2019; Available onlineHow to Cite This Article: Monteiro, W.M.L., and Sarmento, A (2019). Analysing the Possibility of Extracting Energy from Ocean Waves in Cabo-Verde to Produce Clean Electricity - Case-Study: The Leeward Islands. Int. Journal of Renewable Energy Development, 8(1), 103-112https://doi.org/10.14710/ijred.8.1.103-112